O jongo e o moçambique no Vale do Paraíba (1988 2014): cultura, práticas e representações - Cruz, Luiz Paulo Alves da (2015)
This study examines the cultural and religious manifestations of jongo and moçambique in the Vale do Paraíba from 1988 to 2014. We seek to rebuild their identity, through the memory of jongueiros and moçambiqueiros. And from the analysis of the sources, we aimed to understand their ways to convey the story through expressions performed during their festivities, the orallity was vital support for transmission of knowledge, with the stories, memories and African-Brazilian traditions. Thus, there were the interpretation of costumes, instruments, signs and symbols. During their celebrations we find linkages with the African continent, particularly Africa Bantu, constituting the Africanities. Members of jongo and moçambique are descendants of slaves who last created these cultural and religious events as a form of resistance and that influenced Brazilian social, cultural and religious formation